The Influence of Self-Regulation on Students’ Academic Resilience: A Curriculum Development Perspective - Saifulloh, Ahmad; Hasanah, Zulfa Uswatun (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
Several educational experts assert that self-regulation is a critical factor influencing students’ academic resilience. This study aims to test that thesis by investigating the influence of self-regulation on the academic resilience of pesantren students. This influence is framed within curriculum development perspective seeing curriculum as the broading meaning comprising list of subjects and learning experiences. The research employed a quantitative approach, utilizing an associative survey method involving 168 second-year female students at Pesantren Gontor Putri, Campus 3, Ngawi, East Java. Data were analyzed using descriptive statistics and simple linear regression. The findings revealed that 81 students demonstrated a high level of self-regulation, while 115 students exhibited a high degree of academic resilience. Furthermore, the regression analysis produced a significance value of 0.00, which is below the 0.05 threshold, indicating that alternative hypothesis (Ha) is accepted. This means, there is an influence of self-regulation on academic resilience among female students at Gontor Putri. These findings underscore the importance fostering students' self-regulation skills as a means to sustain academic resilience within pesantren curricular systems.